2021
DOI: 10.1021/acsomega.1c05259
|View full text |Cite
|
Sign up to set email alerts
|

Four Autophagy-Related Long Noncoding RNAs Provide Coexpression and ceRNA Mechanisms in Retinoblastoma through Bioinformatics and Experimental Evidence

Abstract: Retinoblastoma (RB) is the most common type of intraocular malignant tumor that lowers the quality of life among children worldwide. Long noncoding RNAs (lncRNAs) are reported to play a dual role in tumorigenesis and development of RB. Autophagy is also reported to be involved in RB occurrence. Although several studies of autophagy-related lncRNAs in RB have been explored before, there are still unknown potential mechanisms in RB. In the present study, we mined dataset GSE110811 from the Gene Expression Omnibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Computational analysis of lncRNA-miRNA-mRNA interactions would provide a theoretical basis for the molecular mechanism of disease, and for the identification of potential therapeutic targets [ 92 ]. However, to our knowledge only a single study has demonstrated autophagy-related lncRNA-miRNA-mRNA regulatory networks in RB [ 93 ]. Thus, we investigated the direct interactions between lncRNA-miRNA, miRNA-mRNA and lncRNA-mRNA, and constructed lncRNA-miRNA-mRNA network.…”
Section: Discussionmentioning
confidence: 99%
“…Computational analysis of lncRNA-miRNA-mRNA interactions would provide a theoretical basis for the molecular mechanism of disease, and for the identification of potential therapeutic targets [ 92 ]. However, to our knowledge only a single study has demonstrated autophagy-related lncRNA-miRNA-mRNA regulatory networks in RB [ 93 ]. Thus, we investigated the direct interactions between lncRNA-miRNA, miRNA-mRNA and lncRNA-mRNA, and constructed lncRNA-miRNA-mRNA network.…”
Section: Discussionmentioning
confidence: 99%
“…Shao et al suggested that SH3BP5-AS1 may engage in natural killer cell-mediated cytotoxicity [ 40 ], which is directly regulated by autophagy [ 41 ]. Related studies have shown that abnormalities in the lncRNA SH3BP5-AS1 are associated with poor prognosis in patients with retinoblastoma by activating carcinogenic autophagy [ 42 ]. LncRNA SH3BP5-AS1 can also serve as a necroptosis-associated lncRNA and is included in the necroptosis-associated lncRNA model for predicting breast cancer prognosis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, significant inroads have been made in our understanding of the role of lncRNAs. The various functions of lncRNAs affect different aspects of physiology, such as cell cycle regulation, cell differentiation, gene post-transcriptional regulation and responses to diverse stresses and stimuli ( Chen et al, 2019 ; Zottel et al, 2020 ; Ren et al, 2021 ). LncRNAs can reportedly compete for miRNA binding, thereby modulating the expression of genes.…”
Section: Discussionmentioning
confidence: 99%